Formula-Based Approach in Allocation of Specific Allocation Grants for Infrastructure (DAK Fisik): Case of Education Provision - Tengku Munawar Chalil; Mohammad Roudo (Jurnal Perencanaan Pembangunan: The Indonesian Journal of Development Planning, 2020)
The paper presents the top-down (formula-based) approach in allocation of specific purpose grants for infrastructure (DAK fisik) in education by considering the needs of infrastructure in education. First, we estimate the needs of education infrastructure by calculating the gap between current condition of infrastructures and the minimum required infrastructures in education. Then, we translate the needs into necessary costs for education per region. After that, we simulate the financial scenario for the necessary costs using specific allocation grants in hierarchical, temporal and regional dimension. We also consider the local fiscal capacity and indicators on achievement of local governments in education for the distribution on DAK Fisik for FY2021 and onwards. Finally, we provide potential implication of formula-based approach as a top-down planning and budgeting for DAK Fisik.